The Effect of the Audio Stimulus Types on Students’ Concentration Level - Megasari Kurnia; Ilham Bakri; Retnari Dian Mudiastuti; Nadzirah Ikasari Syamsul; Priscillia Ingrid Tanditasik (Industrial Engineering Study Program, Pattimura University, 2024)
Concentration is essential in order to help to perceive and understand the object that is being focused. If students can concentrate, everything can be recorded properly in the brain's memory. If student concentration experiences obstacles in learning activities, there will be obstacles to achieve goals. This study aims to analyze the influence and relationship between concentration levels when listening to different audio stimuli. The methods that can be used quantitatively to see learning concentration are reaction time and memory recall methods for 30 students. The data obtained are processed using statistical tests, that is the T test and ANOVA test to test the differences in sample means from different variables and draw conclusions by finding different data groups. Based on the results of the T test, giving the three audio stimuli to men did not provide a significant average difference in reaction speed. Meanwhile, for female respondents, only the favorite song stimulus had a significant average difference. There is no significant difference in memory recall ability to audio stimulus. For the male respondents, the instrumental stimulus was the most effective stimulus, while for the female, the favorite song stimulus was the most effective.